The Effect of Gelatine Colloid Preloading on Hypotension Prevention in Cesarean Section with Spinal Anesthesia at The Central Surgery Installationof Banyumas Regional Hospital - Kuat Widodo; Nur Isnaini (Proceedings Series on Health & Medical Sciences, 2024)
Background:Hypotension in cesarean-section patients occurs due to peripheral vasodilation. It was the result of a sympathetic blockade caused by spinal anesthesia medication. Several methods can be employed to manage hypotension during cesarean section surgery, including fluid loading and vasopressors. Preloading with colloid fluids like hydroxyethyl starch (HES) before initiating spinal anesthesia has been deemed effective in reducing the incidence and severity of hypotension. A preliminary study revealed a decrease in blood pressure (up to 20%) in the first 15 minutes after spinal anesthesia was given to 30 cesarean section patients.Method: In this research, a Quasi-Experimental method was employed with a Pretest-Posttest Control Group Design. A total of 94 respondents were selected as the research sample using a purposive sampling technique. The respondents were divided into two groups: the ephedrine group and the preloading group. The data obtained were then analyzed using Independent Sample T-Test. Results:There is a significant effect on systolic and diastolic blood pressure between the ephedrine and preloading group, with respective significance values of p 0.010 and p 0.001. Conclusion:Preloading gelatine colloid is effective in maintaining blood pressure (systolic and diastolic) in cesarean section patients with spinal anesthesia.